PENGARUH MOTIVASI DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN (Studi Pada Bank Kalsel Syariah Kandangan) - Sri Winarsih; Ahmad Alim Bachri; Akhid Yulianto (Universitas Lambung Mangkurat, 2018)
Results of multiple linear regression analysis in this study produces constant of 0354 stating that if there is no work Morivasi ( x1 ) and job satisfaction ( x2 ) then job satisfaction is equal to 0.354 . Regression coefficient of work motivation ( x1 ) of 0.396 states that any additions ( as a positive sign ) 1 point will increase the job satisfaction of job satisfaction on job satisfaction assuming 0.396 ( x2 ) fixed . Job satisfaction regression coefficient ( x2 ) of 0.688 states that any additions ( as a positive sign ) 1 point of work motivation will increase employee job satisfaction in 0688 with the notion of work motivation ( x1 ) remains.Significant test simultaneously / together ( test statistic F ) result in calculated F value of 78 145. At Kalsel Bank Syariah Kandangan or it can be said that the work motivation ( x1 ) and job satisfaction ( x2 ) jointly affect the performance of employees at Bank Syariah Kandangan South Kalimantan. Calculations using the t -test, concluded that motivation is a significant effect on the performance of employees at Bank Syariah Kandangan Kalsel zero hypothesis ( Ho ) is rejected and Ha accepted, so this hypothesis has been tested empirically